IMPROVE THE EFFICIENCY OF SEISMIC WITH RUBBER MOUNTS ELEMENTS COMBINED WITH DRY FRICTION - A. D. Abakarov; Kh. M. Omarov (Вестник Дагестанского государственного технического университета: Технические науки)
The goal is to increase effectiveness of seismic isolation of buildings with flexible rubber-seismic isolation bearings (RSIB). In order to reduce the maximum displacement RSIB installed in the basement of frame buildings in seismic isolation system introduced elements of dry friction. By integrating the original system of differential equations of motion of the systems under consideration, the parameters of the seismic response of horizontal seismic shear forces, the maximum movement of the masses and maximum displacements RMSO in a wide range of seismic predominant period of the ground motion. By comparing the graphs and tables show the values of seismic response of seismic isolation system combining an advantage with rubber mounts with the elements of dry friction.